2022
DOI: 10.1007/s10803-022-05624-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of moment-to-moment dynamics of perceived stress and negative affect in co-occurring ADHD and internalising symptoms

Abstract: A maladaptive response to stress in individuals with high ADHD traits may be a key factor explaining co-occurring ADHD symptoms and internalising problems. The current study investigates whether between-person differences in ADHD traits are associated with differences in the within-person moment-to-moment coupling of stress and negative affect; and whether these can explain between-person differences in internalising problems (N = 262, median-age 20). Results of a dynamic structural equation model indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The between‐level ω estimates internal consistency reliability when measuring individuals' overall levels of stress. This is important for examining sources of individual differences in perceived stress, such as whether individuals with higher levels of depression or ADHD symptoms tend to experience higher overall levels of perceived stress (Speyer et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The between‐level ω estimates internal consistency reliability when measuring individuals' overall levels of stress. This is important for examining sources of individual differences in perceived stress, such as whether individuals with higher levels of depression or ADHD symptoms tend to experience higher overall levels of perceived stress (Speyer et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the current sample, Speyer et al. (2022) investigated the role of moment‐to‐moment dynamics of perceived stress and negative affect in co‐occurring ADHD and internalising symptoms. They found that ADHD traits were associated with increased stress reactivity, with stress carry‐over further mediating the association between ADHD symptoms and internalising problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 For example, EMA data can be used to provide measures of different aspects of emotional functioning in daily life, such as overall levels of negative affect, affective lability, emotional inertia and emotional reactivity to stressors or provocations. 24 25 …”
Section: Introductionmentioning
confidence: 99%
“…To date, DSEM has been primarily used within clinical psychology or adjacent research areas, however, as intensive longitudinal data collection is becoming more prominent, so is the use of DSEM in other research areas, for instance in cognitive neuroscience (McCormick & Kievit, 2023). DSEM has been used to investigate research questions focusing on directional associations between within-person components (Blanke et al, 2021;Metcalf et al, 2021), to gain insights into whether between-person factors (such as ADHD traits) moderate within-person effects (Aristodemou et al, 2022;Brown et al, 2022), to evaluate whether within-person effects (such as stress reactivity) mediate the associations between two between-person factors (Speyer et al, 2022) and to investigate mediation effects on the within-person level (McNeish & Mackinnon, 2022). For example, Blanke et al (2021) used a DSEM to investigate the within-person dynamics between rumination and negative affect.…”
Section: Introductionmentioning
confidence: 99%